Analyst Coverage, Information, and Bubbles - Andrade, Sandro C.; Bian, Jiangze; Burch, Timothy R. (Journal of Financial and Quantitative Analysis, 2013)
Abstract We examine the 2007 stock market bubble in China. Using multiple measures of bubble intensity for each stock, we find significantly smaller bubbles in stocks for which there is greater analyst coverage. We further show that the abating effect of analyst coverage on bubble intensity is weaker when there is greater disagreement among analysts. This suggests that, in line with resale option theories of bubbles, one channel through which analyst coverage may mitigate bubbles is by coordinating investors’ beliefs and thus reducing its dispersion. Stock turnover provides further evidence consistent with this particular information mechanism.